Lip pattern types among mandailing bataknese and sundanese in padang city, sumatera barat province, indonesia: Study cross-sectional - Amalia, Afifah Fitri; Nismal, Harfindo; Sari, Desy Purnama (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The immigrant community from West Sumatra comes from various ethnic groups in Indonesia, including Batak Mandailing (proto-Malay) and Sundanese (deutro-Malay). West Sumatra is known as a